Are Populist Leaders Creating the Conditions for the Spread of COVID-19?; Comment on "A Scoping Review of Populist Radical Right Parties' Influence on Welfare Policy and its Implications for Population Health in Europe" - Martin McKee; Alexi Gugushvili; Jonathan Koltai; David Stuckler (Kerman University of Medical Sciences, 2021)
Do populist leaders contribute to the spread of coronavirus disease 2019 (COVID-19)? While all governments have struggled to respond to the pandemic, it is now becoming clear that some political leaders have performed much better than others. Among the worst performing are those that have risen to power on populist agendas, such as in the United States, Brazil, Russia, India, and the United Kingdom. Populist leaders have tended to: blame "others" for the pandemic, such as immigrants and the Chinese government; deny evidence and show contempt for institutions that generate it; and portray themselves as the voice of the common people against an out-of-touch 'elite.' In our short commentary, focusing on those countries with the most cases, we find that populist leaders appear to be undermining an effective response to COVID-19. Perversely, they may also gain politically from doing so, as historically populist leaders benefit from suffering and ill health. Clearly more research is needed on the curious correlation of populism and public health. Notwithstanding gaps in the evidence, health professionals have a duty to speak out against these practices to prevent avoidable loss of life.